Opini Pengguna Twitter Terhadap Upaya Memaafkan Yang Dilakukan Oleh Lesty Kejora Atas Kasus KDRT - Hatijah, Mita; Shasrini, Tessa (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this research is to analyze the opinions of twitter users who follow the account of @komnasperempuan on the efforts to apologize in the domestic violence case experienced by Lesty kejora on twitter social media. this research uses descriptive qualitative methods. In conducting this research, the data collection techniques used are interviews and documentation. The data analysis used is the theory of Miles and Huberman, the analysis activity consists of three streams of activities that occur simultaneously, namely data reduction, data presentation, and conclusion drawing / verification. The result of this research shows that Lesty Kejora's effort to forgive is an inappropriate action as a public figure.